2002
DOI: 10.1161/01.cir.0000018653.19696.01
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Wine and Beer Consumption in Relation to Vascular Risk

Abstract: Background-Many epidemiological studies have evaluated whether different alcoholic beverages protect against cardiovascular disease. We performed a meta-analysis of 26 studies on the relationship between wine or beer consumption and vascular risk. Methods and Results-General variance-based method and fitting models were applied to pooled data derived from 26 studies that gave a quantitative estimation of the vascular risk associated with either beverage consumption. From 13 studies involving 209 418 persons, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
1
7

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 495 publications
(164 citation statements)
references
References 56 publications
7
149
1
7
Order By: Relevance
“…In a meta-analysis of wine and beer consumption in relation to cardiovascular disease risk, Di Castelnuovo [34] suggested that women might be particularly responsive to alcohol itself rather than to the nonalcoholic components. Our results were consistent with their meta-analysis findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of wine and beer consumption in relation to cardiovascular disease risk, Di Castelnuovo [34] suggested that women might be particularly responsive to alcohol itself rather than to the nonalcoholic components. Our results were consistent with their meta-analysis findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, some epidemiological studies have suggested that light to moderate ethanol consumption has protective effects against several diseases including chronic heart diseases (7,8) and ischemic stroke (9).…”
mentioning
confidence: 99%
“…An inverse association between moderate alcohol consumption and CHD has been consistently shown in many epidemiological studies [1][2][3][4][5][6][7][8][9][10], but important issues remain to be clarified.…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…Schematic effect of polyphenol-poor gin or red wine intake on different biochemical parameters in healthy subjects modified from reference 41, with permission tality rates in France (the "French Paradox") [7], and many subsequent epidemiological studies have explored the French-paradox-generated hypothesis. We reviewed such studies in two meta-analyses based on 26 articles (including more than 200,000 persons) reporting comparisons between wine and beer and the risk of CHD [1]. The overall relative risk (RR) of wine drinkers in respect to non drinkers was 0.68 (95% confidence interval (95% CI): 0.59-0.77), whereas the protection associated with beer drinking was 10% lower (in absolute terms).…”
Section: Differences Among Different Alcoholic Beveragesmentioning
confidence: 99%
See 1 more Smart Citation